Molecular evidence of Monocercomonas and Acanthamoeba in the feces of captive reptiles - Tuska-Szalay, Barbara; Kelly, Hannah; Takács, Nóra; Kontschán, Jenő; Votýpka, Jan; Hornok, Sándor (Parasitology research, 2022)
Reptiles are frequently kept as pet animals. They are considered as important reservoirs of protozoa with veterinary-medical significance. At a reptile farm in Ireland, fecal samples were collected from 98 captive reptiles, representing 43 species of three orders (Squamata, Testudines, and Crocodylia). After DNA extraction, all samples were screened by conventional PCRs, targeting the ribosomal small subunit (SSU) RNA and alpha-tubulin genes of trichomonads and SSU RNA gene of Acanthamoeba spp. One leopard gecko (Eublepharis macularius) was positive for a not yet reported species/genotype of the genus Monocercomonas, different from M. colubrorum. Various Acanthamoeba genotypes were detected in six reptilian species, i.e., Acanthamoeba genotype T11 in Eunectes notaeus and Heloderma suspectum/horridum; genotype T4 in Varanus exanthematicus, Chlamydosaurus kingii, and Macrochelys temminckii; and the genotype T13 in Iguana iguana. Some of these amoeba species might have clinicopathological significance in both humans and animals. Our findings highlight the importance to monitor pathogenic protozoa in pet as well as wildlife reptiles, as a source of possible infection for animals and humans living nearby.
Keywords: Animals; SSU rRNA gene; Protozoa; Trichomonadea; lidé; Amoeba; Trichomonadida; zvířata; feces; plazi; Reptiles; genotyp; Genotype; Feces; Squamata; RNA; Acanthamoeba; Humans